PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT ISS INDONESIA AREA GELORA BUNG KARNO - Rykky Bond Santufo Silaban; I Made Aryata (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of training and career development on the performance of PT ISS Indonesia employees in the Gelora Bung Karno area partially and simultaneously. The method used was quantitative. The population in this study amounted to 327 respondents. The sampling technique used the Slovin Formula and obtained 77 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study are that training has a significant positive effect on employee performance as evidenced by the hypothesis test obtained t count> t table or (7.242> 1.992) and strengthened by a significance of 0.000 <0.05, the regression equation obtained Y = 14.852 + 0.515X1, correlation coefficient 0.641 with a strong relationship level and a determination coefficient value of 41.2%. Career development has a significant positive effect on employee performance as evidenced by the hypothesis test obtained t count > t table or (7.405 > 1.992) and strengthened by a significance of 0.000 < 0.05, the regression equation obtained Y = 18.500 + 0.524X2, a correlation coefficient of 0.650 with a strong relationship level and a determination coefficient value of 42.2%. Training and career development simultaneously have a significant positive effect on employee performance as evidenced by the hypothesis test obtained the calculated F value > F table or (43.401 > 2.730) and reinforced with a significance of 0.000 < 0.05 with the regression equation Y = 10.422 + 0.328X1 + 0.344X2, correlation coefficient 0.735 with a strong relationship level and a determination coefficient value of 54.0% while the remaining 46.0% is influenced by other variables.